Genetic Alteration Analysis of IDH1, IDH2, CDKN2A, MYB and MYBL1 in Pediatric Low-Grade Gliomas - Barinfeld, Orit; Zahavi, Alon; Weiss, Shirel; Toledano, Helen; Michowiz, Shalom; Goldenberg-Cohen, Nitza (Frontiers in Surgery, 2022)
Objective: To investigate pediatric low-grade gliomas for alterations in IDH1, IDH2, CDKN2A, MYB, and MYBL1. Materials and Methods: DNA and RNA were extracted from 62 pediatric gliomas. Molecular methods included PCR, RT-PCR, and RNA sequencing; Sanger sequencing was used for validation. Results: Analysis for hotspot genetic alterations in IDH1 R132 and IDH2 R172 (45 and 33 samples) was negative in all cases. CDKN2A deletions were detected in exons 1 and 2 in 1 (pleomorphic xanthoastrocytoma) sample of 9 samples analyzed. Of 10 samples analyzed for MYB translocation, 4 each were positive for translocations with exon 2 and exon 3 of PCDHGA1. Six samples showed MYBL rearrangement. The lack of IDH1/2 genetic alterations is in accordance with the literature in pediatric tumors. Alterations in MYB, MYBL were recently reported to characterize diffuse grade II, but not grade I, gliomas. Conclusion: We optimized methods for analyzing gene variations and correlated the findings to pathological grade. The high incidence of MYB and MYBL need further evaluation. We also compared DNA, RNA, and RNA sequencing results for fusion, translocation, and genetic alterations. More accurate identification of the underlying biology of pediatric gliomas has implications for the development of targeted treatment.